Relationship between number of brushings per day and periodontal index in 12-year-old schoolchildren from the San Blas parish, Cuenca, Ecuador. 2016. - Cabrera González, Carmen Guadalupe (2021)
Tooth brushing is important as a hygiene measure and for removing dental plaque. Periodontal disease is one of the diseases that often affects humans causing the loss of their dental parts. Objective: Relate the daily frequency of brushing with the Russell periodontal index in a school population of the San Blas parish of the city of Cuenca, Ecuador. Method: Observational, cross sectional study where information was collected from 166 schoolchildren 12-year-old whose epidemiological history is found in the database of the Research Department of the Dental Career of the Catholic University of Cuenca. Descriptive statistics process the variables: sex, daily brushing frequency and Russell periodontal index and the correlation (Kendall) between brushing and periodontal index was sought. Results: There was a predominance of women (57%). The onset of periodontal disease in them was 10.5% and in males 9.9%. Brushing three times a day was done in 60.8% of schoolchildren, less than three times 35.5% and more than three times, only 3%. The correlation between brushing frequency and periodontal index was very low, only 0.16 (P > 0.05). Conclusion: However, the validity of the classic concept, that infrequent brushing is associated with severe forms of periodontal disease, some researchers argue that studies that correlate the frequency of brushing with periodontitis are needed to obtain conclusive data.